Association between viral load and positivization time of a SARS-CoV-2 rapid antigen test in routine nasopharyngeal specimens: Viral load and time to rapid SARS-CoV-2 antigen test positivization - Salvagno, Gian Luca; Henry, Brandon Michael; De Nitto, Simone; Pighi, Laura; Lippi, Giuseppe (Journal of Medical Biochemistry, 2022)
Background: Rapid SARS-CoV-2 antigen tests are potentially useful tools for screening carriers with high viral load. This study was aimed to assess the potential association between viral load and positivization time of a manual SARS-CoV-2 commercial antigen test in routine nasopharyngeal specimens.Methods: In a sample of subjects undergoing routine diagnostic testing, SARS-CoV-2 positivity of nasopharyngeal samples was assayed with both molecular (Altona Diagnostics RealStar SARS-CoV-2 RT-PCR Kit) and antigenic (Roche SARS-CoV-2 Rapid Antigen Test) tests. Positivization time of rapid antigen test was correlated and compared with viral load expressed as mean of SARS-CoV-2 E/S genes cycle threshold (Ct) values.Results: The study sample consisted of 106 patients (median age 48 years, 55 women) with positive results of rapid SARS-CoV-2 antigen testing. A highly significant Spearman’s correlation was found between mean SARS-CoV-2 E/S genes Ct values and positivization time of manual antigen test (r= 0.70; p
Keywords: COVID-19; SARS-CoV-2; Laboratory Medicine; Diagnosis; Immunoassay